Resilience in Chaos: Sudanese Actors Shock Absorber in Catastrophes - Elsheikh, Mohamed; Ibrahim, Mona; Walton, Abi; K Osman, Alhadi (Sudan Journal of Medical Sciences, 2024)
This is an Editorial and does not have an abstract. Please download the PDF or view the article in HTML.